The power of group work: personal recollections on Peter Bruggen. (September 2019) - Ezquerro, Arturo
This article aims to honour Peter Bruggen (17 July 1934–20 September 2018) who has been one of the great influences on adolescent mental health and, from my perspective, on innovative 'group-analytic', psychotherapy. Inspired by the work and ideas of Donal Winnicott, Derek Miller, Tom Main and SH Foulkes, Bruggen created an in-patient adolescent unit where all therapeutic work took place in groups. He supported the authority of the parents and, also, the developing authority of the adolescents to help them develop a sense of inner authority which they could recognize as their own.